Conceptual Framework on Usage of Islamic Banking amongst Banking Customers in Libya - Albashir, Walid Ali; Yuserrie, Zainuddin; Panigrahi, Shrikant (Universiti Teknologi Malaysia - IBS, 2017)
The main purpose of this paper is to increase customer perception for Islamic banking products and its awareness in Libya. There has been an urgent requirement of Islamic banking in the Libyan banking system due to economic turbulence and being unable to maintain national finances. Libyan banks have already implemented Islamic banking system as an alternative to the conventional system, however, the adoption of Islamic products is not widely accepted by customers. Based on literature done regarding adoption studies, this paper suggests and justifies the applicability of Ajzen’s Theory of Planned Behaviour in Islamic banking adoption. From literature review and conceptual framework, lack of attitude and behaviour of customers on Islamic banking product acceptance is a great challenge for Libyan Islamic banks. Therefore, there is a need for marketing efforts by banks to increase awareness, perception, and intention of Libyan banking customers in relation to Islamic banking.